Analysis of the Predictive Value of Procalcitonin and C-Reactive Protein for Coalescent Mastoiditis in Pediatric Patients: A Narrative Review - Hanief Rifqi Falih; Hanimmatul Udmanurlaili; Muhammad Adnan; Raihan Daffa Al-Ghiffary; Mumtaz Al-Mukaffa; Dodik Nursanto (UMSU, 2026)
Abstract: Coalescent mastoiditis (CM) is a severe complication of acute otitis media in children for which definitive diagnosis requires a CT scan, creating a clinical need for non-invasive biomarkers. This narrative review aims to evaluate the roles of C-reactive protein (CRP) and procalcitonin (PCT) as predictors of CM. The methodology involved a structured literature search of databases including PubMed and Scopus for publications within the last five years (2020-2025). The results indicate that CRP is a reliable biomarker, with a level of ≥98.7 mg/L predicting the need for surgical intervention with 100% sensitivity and 74.6% specificity. Conversely, evidence for PCT is significantly lacking; indirect data suggest its levels do not consistently increase in localized infections such as CM. In conclusion, CRP is a validated and clinically useful biomarker for the risk stratification of CM in children, whereas the role of PCT remains unproven and appears to be limited.